2018
DOI: 10.12717/dr.2018.22.1.095
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cyclic AMP-Response Element Binding Protein Zhangfei (CREBZF) Expression by Estrogen in Mouse Uterus

Abstract: CREBZF (cAMP-response element binding protein zhangfei) is a member of ATF/CREB family, and which regulates various cellular functions by suppressing major factors with direct interaction. In this study, we have examined the expression of CREBZF on mouse endometrium during uterus estrous cycles and estrogen (E2) treatment. In uterus, CREBZF mRNA expression was higher than other organs and mRNA and protein of CREBZF was increased in proestrus phase and decreased in estrus phase. The expression of CREBZF in 3-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…We determined the localization of CREBZF in the ovaries, showing that CREBZF is widespread in the ovarian tissue, especially in granulosa cells and oocytes, and significantly increases during the proestrus and estrous phases. Consistent with a previous study, CREBZF is expressed at high levels in the luminal and glandular epithelium of the uterus at the proestrus and oestrus phases [ 25 , 26 ]. We speculated that CREBZF might participate in follicular development and be regulated by the sex hormones in the reproductive system.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We determined the localization of CREBZF in the ovaries, showing that CREBZF is widespread in the ovarian tissue, especially in granulosa cells and oocytes, and significantly increases during the proestrus and estrous phases. Consistent with a previous study, CREBZF is expressed at high levels in the luminal and glandular epithelium of the uterus at the proestrus and oestrus phases [ 25 , 26 ]. We speculated that CREBZF might participate in follicular development and be regulated by the sex hormones in the reproductive system.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, a study reported that CREBZF plays a potential role in mediating uterine receptivity during the implantation and development of preimplantation embryos in mice [ 25 , 26 ]. Moreover, CREBZF is regulated by activating blastocysts and estrogen (E2) in mouse uteri, and SMILE is the main isoform of CREBZF in this process [ 25 ].…”
Section: Introductionmentioning
confidence: 99%